Evaluation of the Pressure Ulcer Prevention Clinical Decision Report for Bedside Nurses in Acute Care Hospitals - Talsma, A.; Tschannen, D.; Guo, Y.; Kazemi, J. (Applied Clinical Informatics, 2011)
Background: Hospital stays for patients with pressure ulcers (PU) increased nearly 80% from 1992 to 2006. Most PU’s developed during an admission, often despite preventive efforts from clinical staff. Data from Electronic medical records (EMR’s) were used to prepare daily patient risk factor and PU information for nurses to help prevent PU development and exacerbations.Objectives: The objectives of this study were to determine whether: 1) dissemination of an automated daily report with patient risk and current status of pressure ulcers (“PU Daily”) helps prevent the development of pressure ulcers, and 2) using the PU Daily information impacts the severity of pressure ulcers that develop in an acute care setting.Methods: A pre-post study with four control units was designed to determine the impact of the PU Daily in intensive care units (ICU) in a large medical center. The control units included ICU’s using the same EMR and similar complexity of cases with a high risk of developing a PU. The pre-post study took place over a six month period (March – August 2009).Results: A total of 6,735 cases were included in the study. The intervention unit showed a significant decrease (p = 0.004) in PU’s at post-evaluation; none of the four comparison units showed a decrease at the p<0.05 level. The intervention led to a significant reduction in the total number of PU’s documented (p <0.000) and the number of Stage II PU’s (p = 0.046).Conclusion: The intervention with the PU Daily showed a significant decrease in the total PU’s and severity of PU’s and allowed for implementation of interventions that help prevent the development of PU’s. As EMR’s become more widely available, this intervention showed a reduction in PU’s. Future studies should further develop this intervention and include multiple institutions and patient populations.
Keywords: Electronic medical records; EMR; ICU; intervention; pressure ulcers; prevention